2022
DOI: 10.3390/ijerph192315453
|View full text |Cite
|
Sign up to set email alerts
|

Calling for Help—Peer-Based Psychosocial Support for Medical Staff by Telephone—A Best Practice Example from Germany

Abstract: Background: A telephone support hotline (PSU-HELPLINE) was established at the beginning of the pandemic due to the burden on health professionals and the lack of support at the workplace. The aim of this study was to evaluate the telephone support service for health professionals in terms of its burden, benefits, and mechanisms of action. Methods: Data collection was conducted during and after calls by PSU-HELPLINE counsellors. In addition to the socio-demographic data evaluation, burdens of the callers and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We found that in some cases the organisational environment was beneficial to the implementation of the programme, particularly when healthcare organisations were already working towards creating a more supportive environment for their staff and strengthening the safety culture 36 37 42 43 56 60…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We found that in some cases the organisational environment was beneficial to the implementation of the programme, particularly when healthcare organisations were already working towards creating a more supportive environment for their staff and strengthening the safety culture 36 37 42 43 56 60…”
Section: Resultsmentioning
confidence: 98%
“…Some of the programmes were implemented in healthcare organisations where some PS initiatives and ‘culture-shifting interventions’ had already taken place 37 39 50 55. In other cases they were integrated in major projects developed by the organisations 42 56 60. Both situations were considered potential facilitators for maintaining the programmes over time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations